Pengaruh Scrapbook terhadap Perilaku Personal Hygiene Menstruasi pada Remaja Putri - Nuril Khazinatul Asror; Desi Rofita; St. Halimatusyaadiah; Baiq Iin Rumintang (Midwifery Student Journal (MS Jou), 2026)
Latar Belakang: Perilaku personal hygiene saat menstruasi penting untuk mencegah infeksi pada remaja putri, namun praktiknya masih rendah akibat kurangnya pendidikan kesehatan. Tujuan: Menganalisis pengaruh pendidikan kesehatan reproduksi menggunakan media scrapbook terhadap perilaku personal hygiene saat menstruasi pada remaja putri. Metode: Penelitian menggunakan desain pre-experimental one-group pretest–posttest pada 46 siswi kelas VII dan VIII. Data dianalisis menggunakan uji Wilcoxon. Hasil: Sebagian besar responden berusia 13 tahun (52,2%), mengalami menarche pada usia 12 tahun (80,4%), lama menstruasi 5–7 hari (63,0%), dan memperoleh informasi dari keluarga (37,0%). Rata-rata skor perilaku personal hygiene meningkat dari 44,91 sebelum intervensi menjadi 59,89 setelah intervensi. Uji Wilcoxon menunjukkan perbedaan yang bermakna (p=0,001). Kesimpulan: Pendidikan kesehatan menggunakan scrapbook efektif meningkatkan perilaku personal hygiene saat menstruasi pada remaja putri. Abstract Background: Adolescence is characterized by biological changes, including menstruation. Adolescent girls need to maintain good personal hygiene during menstruation to prevent reproductive tract infections. A preliminary study at SMP IT Al-Kamal NW Narmada found that many female students did not change sanitary pads regularly and had inadequate personal hygiene practices due to limited health education. Scrapbook media, as a visual educational tool, is considered attractive and easy to understand, making it a potential medium for improving such behaviors. Objective: To determine the effect of reproductive health education using scrapbook media on menstrual personal hygiene behavior among adolescent girls. Methods: This study employed a pre-experimental one-group pretest–posttest design involving 46 female students from grades VII and VIII. Data were analyzed using the Wilcoxon signed-rank test. Results: Most respondents were 13 years old (52.2%), experienced menarche at the age of 12 years (80.4%), had a menstrual duration of 5–7 days (63.0%), and had previously received information about menstruation and personal hygiene (63.0%), primarily from their families (37.0%). The mean personal hygiene behavior score increased from 44.91 before the intervention to 59.89 after the intervention. The Wilcoxon test showed a statistically significant difference (p = 0.001). Conclusion: Reproductive health education using scrapbook media was effective in improving menstrual personal hygiene behavior among adolescent girls.